Depth‐Resolved Photochemical Lability of Dissolved Organic Matter in the Western Tropical Pacific Ocean. Issue 3 (18th March 2020) - Yang, Fangming; Song, Guisheng; Massicotte, Philippe; Wei, Hao; Xie, Huixiang
Abstract: Water samples collected from various depths of the offshore South China and Philippine Seas were exposed to solar‐simulated radiation. Photomineralization of dissolved organic carbon (DOC) and photobleaching of chromophoric dissolved organic matter (CDOM) and its humic‐like fluorescent constituent (FDOM) were observed in all samples. Protein‐like FDOM was, however, either photo‐decomposed or photo‐produced, depending on the sample's depth. The photobleaching of CDOM and humic‐like FDOM was much faster in deep than in shallow water samples while photomineralization displayed a weaker vertical zonation. Prior‐irradiated deep water inoculated with surface‐water bacteria showed enhanced microbial DOC removal but CDOM production. Results from this study suggest that deep‐ocean CDOM and FDOM can barely survive photobleaching during one ocean mixing cycle, but photochemical turnover of the bio‐refractory deep DOC is considerably longer than its average radiocarbon age. Coupled photochemical‐microbial processes can not only remove part of the bio‐refractory deep DOM but also regenerate part of it during ocean overturning circulation. Plain Language Summary: The production, consumption, and transformation of dissolved organic matter (DOM) in the ocean play a key role in climate change, since the oceanic DOM stock in terms of carbon is similar to the amount of atmospheric CO2 . The majority of oceanic DOM is contained in the deep ocean and resists bacterial degradation, which allows the deep DOM to pass through the sunlit surface ocean multiple times during its life span by means of large‐scale ocean currents. Part of DOM is colored (CDOM), absorbs sunlight, and undergoes light‐initiated chemical (i.e., photochemical) alteration, producing CO2 (i.e., photomineralization) and/or colorless organic compounds (i.e., photobleaching) consumable by bacteria. The present study compares the photochemical reactivity of CDOM, including its fluorescent component (FDOM), in water samples collected from various depths in the South China Sea and Philippine Sea. CDOM in deep samples was found to be photoreactive and more so than in surface samples in terms of photomineralization and photobleaching. Bacterial incubation in the prior‐irradiated deep water enhanced the biodegradation of DOM to CO2 but, surprisingly, regenerated CDOM from the photochemically produced colorless compounds. Photochemical processes and photochemical‐microbial interactions can thus have a potentially important impact on the transport, transformation, and fate of the deep‐ocean DOM. Key Points: The photolability of chromophoric and humic‐like fluorescent dissolved organic matter in deep water is higher than in surface water The residence time of deep‐ocean dissolved organic carbon with respect to photochemical removal is longer than its average 14 C age Coupled photochemical‐microbial processes remove and regenerate deep‐ocean dissolved organic matter during ocean overturning circulation